ORIGIN OF RODINGITES IN ULTRAMAFIC ROCKS FROM LESVOS ISLAND (NE AEGEAN, GREECE) - Hatzipanagiotou, K.; Tsikouras, B.; Migiros, G.; Gartzos, E.; Serelis, K. (Ofioliti, 2003)
Rodingite dykes occur in serpentinised harzburgites from the southern part of Lesvos Island (Aegean Sea). Based on relict primary textures and chemical data, doleritic protoliths are inferred. The rodingitic assemblage consists mainly of hydrogrossular, chlorite, diopside and epidote. In several cases, a chlorite reaction zone occurs at the rim to the host serpentinite.The rodingitisation process developed in two stages: the formation of hydrogrossular + chlorite, and the formation of the diopside ± epidote and the chlorite reaction zone. This two-stage alteration is associated with the earlier formation of chrysotile + lizardite and then of antigorite, in the host serpentinite. There is a variable extent of element mobility in the rodingites, at constant mass, which is suggestive of diffusional mass-transfer. This behaviour is further supported by the mobility of Ti, Zr, Y and Cr, and the antithetic chemical exchange between the rodingite and the serpentinite. However, a major influence of a hydrothermal fluid phase is indicated by increase of silica activity at the second stage of metasomatism, when the diopside and the antigorite formed in the rodingite and the serpentinite, respectively. Moreover, alteration of the harzburgites cannot account as the only source of the significant Ca amounts required for the rodingitisation, and hence it is likely that considerable amounts of Ca+2 were introduced in the rodingite via a hydrothermal fluid. However, the relatively smaller volume of the rodingite compared to the harzburgite may also account for this Ca-enrichment. Hydrothermal circulation and diffusion were overlapping processes, but the first probably appeared during the second stage of rodingitisation.Initial formation of hydrogrossular and chlorite requires influx of Ca into the system and depletion of Si, whereas subsequent formation of diopside requires influx of Mg. The chlorite reaction zone acted as a channel of high circulation of Mg- and H2O-rich hydrothermal fluids.No direct thermobarometric information can be obtained from the rodingite assemblage. However, considering that chrysotile + lizardite and antigorite are early and late products, respectively, during serpentinisation, their thermal stability fields (up to 350oC for chrysotile + lizardite and 350-500oC for antigorite) are suggestive for temperature increase, during the two stages of the rodingitisation.